Tangkhul Folk Literature - Arokianathan, S. (My University, 1982)
The folk literature collected is used in the linguistic analysis, in the making of dictionaries and the instructional materials, and this literature collected by the field workers includes tales and songs and wherever possible, proverbs and riddles also.
Keywords: English